Benford’s Law and COVID-19 Reporting - Koch, C; Okamura, K (Elsevier, 2020)
Trust in the reported data of contagious diseases in real time is important for policy makers. Media and politicians have cast doubt on Chinese reported data on COVID-19 cases. We find Chinese confirmed infections match the distribution expected in Benford’s Law and are similar to that seen in the U.S. and Italy. We identify a more likely candidate for problems in the policy making process: Poor multilateral data sharing on testing and sampling.